Response to: "letter to the editor regarding the article "the global distribution of acute unintentional pesticide poisoning: estimations based on a systematic review"" by Dunn et al. 2021 in BMC public health - Wolfgang Boedeker; Meriel Watts; Peter Clausing; Emily Marquez (BMC, 2021)
Abstract In a correspondence to BMC Public Health, Dunn et al. (Dunn SE, Reed J and Neumann C. BMC Public Health (n.d)) respond to our review on the occurrence of unintentional, acute pesticide poisoning (UAPP). Based on a systematic review and further data sources we estimated that about 385 million cases of UAPP occur annually world-wide including around 11,000 fatalities (Boedeker W. et al. BMC Public Health:1875, 2020).